Leucemia viral felina em gatos domésticos de Caxias do Sul, Brasil - Diesel, Laura Pancich (My University, 2023)
The feline leukemia virus (FeLV) represents a significant challenge in veterinary clinics worldwide. Several studies have demonstrated a high prevalence of FeLV in various locations in Brazil. Transmission occurs through close contact between infected and susceptible cats. Detection can be performed through immunological (rapid) tests and molecular techniques such as quantitative polymerase chain reaction (qPCR or qRT-PCR), which also allows for viral load assessment. This dissertation aimed to (1) study the frequency of FeLV infections in domestic cats in the municipality of Caxias do Sul and (2) evaluate the viral load data of infected animals. The initial sampling consisted of 598 sequentially attended cats in 7 clinics and 2 veterinary hospitals from January 2022 to March 2023. General information was collected (reason for consultation, residence, age, sex, reproductive status, outdoor access, vaccination), general clinical condition was evaluated, and samples of total blood were collected. From this population, 366 animals with rapid test results for p27 antigen detection using commercial kits at the time of consultation and properly collected blood samples were selected. These samples underwent DNA/RNA extraction and detection/quantification of proviral DNA using qPCR. Samples positive for FeLV proviral DNA were also tested for viral RNA detection/quantification using RT-qPCR. The results showed a total of 112 (30.6%) positive cases in the rapid test and/or qPCR, including males (n=64/112, 57.1%) and females (n=48/112, 42.9%), neutered (n=80/112, 71.3%) and sexually intact cats (n=32/112, 28.6%), with outdoor access (n=76/112, 67.9%) or not (n=34/112, 30.4%), vaccinated (n=36/112, 32.1%) or not (n=74/112, 66.1%). Comparative evaluation of different categories demonstrated that unvaccinated cats (OR 2.52, p < 0.001), clinically ill cats (OR 2.88, p < 0.001), cats with outdoor access (OR 2.70, p < 0.001), and cats with apathetic behavior (OR 3.06, p < 0.001) had higher odds of being infected with FeLV. Among clinical manifestations, lethargy (OR 3.09, p < 0.001), anemia (OR 13, p < 0.001), and neoplasms (OR 5.9, p < 0.001) were more frequent in FeLV-positive animals. Multivariate analysis was performed to verify the correlation of risk factors with FeLV infection, showing statistical significance for unvaccinated cats (OR 9.67; 95% CI: 1.85-23.69) and cats vaccinated with triple (OR 9.67, 95% CI: 3.37-27.76) and quadruple (OR 2.74, 95% CI: 1.53-4.89) vaccines, as well as cats with outdoor access (OR 2.52, 95% CI: 1.49-4.23). Anemia and neoplasia were associated with FeLV infection (OR 9.11, 95% CI: 2.41-29.49 and OR 4.14, 95% CI: 1.42-12.11, respectively). Samples from 103 cats underwent proviral and viral load analysis. Viral and proviral load analyses allowed for preliminary classification of infections as high progressive (n=12/109, 11%), low progressive (n=35/109, 32.1%), and regressive (n=11/109, 10.1%). The high FeLV prevalence demonstrated in this study emphasizes the need to establish effective control and prevention strategies in the region to reduce transmission risk factors. [resumo fornecido pelo autor]
O vírus da leucemia felina (FeLV) representa um desafio significativo nas clínicas veterinárias em todo o mundo. Diversos estudos têm demonstrado alta prevalência de FeLV em vários locais no Brasil. A transmissão ocorre através do contato próximo entre gatos infectados e suscetíveis. Já a detecção pode ser feita por meio de testes imunológicos (rápidos) e técnicas moleculares, como a reação em cadeia da polimerase quantitativa (qPCR ou qRT-PCR) que também permite avaliar a carga viral. Esta dissertação teve como objetivo (1) estudar a frequência de infecções por FeLV em gatos domésticos no município de Caxias do Sul e (2) avaliar os dados de carga viral dos animais infectados. A amostragem inicial consistiu de 598 gatos atendidos sequencialmente em 7 clínicas e 2 hospitais veterinários de janeiro de 2022 a março de 2023. Foram obtidas informações gerais (motivo da consulta, local de residência, idade, sexo, estado reprodutivo, acesso à rua, vacinação), avaliada a condição clínica geral e coletadas amostras de sangue total. A partir dessa população, foram selecionados 366 animais que possuíam resultados de testes rápidos para a detecção do antígeno p27 usando kits comerciais no momento da consulta e tiveram amostras de sangue coletadas adequadamente. Essas amostras foram submetidas à extração de DNA/RNA e detecção/quantificação do DNA proviral usando qPCR. As amostras positivas para o DNA proviral do FeLV também foram testadas para detectar/quantificar o RNA viral usando RT-qPCR. Os resultados demonstraram um total de 112 (30,6%) positivos no teste rápido e/ou qPCR, incluindo machos (n=64/112, 57,1%) e fêmeas (n=48/112, 42,9%), castrados (n=80/112, 71,3%) e gatos sexualmente intactos (n=32/112, 28,6%), com acesso ao exterior (n=76/112, 67,9%) ou não (n=34/112, 30,4%), vacinados (n=36/112, 32,1%) ou não (n=74/112, 66,1%). A avaliação comparativa das diferentes categorias demonstrou que gatos não vacinados (OR 2,52, p < 0,001), clinicamente doentes (OR 2,88, p < 0,001), com acesso ao exterior (OR 2,70, p < 0,001) e com comportamento apático (OR 3,06, p < 0,001) tiveram maiores chances de estarem infectados pelo FeLV. Entre as manifestações clínicas letargia (OR 3,09, p < 0,001), anemia (OR 13, p < 0,001) e neoplasias (OR 5,9, p < 0,001) foram mais frequentes nos animais positivos para FeLV. A análise multivariada foi realizada para verificar a correlação dos fatores de risco com a infecção por FeLV e observou-se significância estatística para gatos não vacinados (OR 9,67; IC 95%: 1,85-23,69) e gatos vacinados com tríplice (OR 9,67, IC 95%: 3,37-27,76) e quádrupla (OR 2,74, IC 95%: 1,53-4,89), além de gatos com acesso ao exterior (OR 2,52, IC 95%: 1,49- 4,23). Anemia e neoplasia estavam associadas à infecção por FeLV (OR 9,11, IC 95%: 2,41, 29,49 e OR 4,14, OR 95%: 1,42-12,11, respectivamente). Amostras de 103 gatos foram submetidas à análise de carga proviral e viral. As análises de carga viral e proviral possibilitaram a classificação preliminar das infecções, sendo classificadas como progressivas altas (n=12/109, 11%), progressivas baixas (n=35/109, 32,1%) e regressivas (n= 11/109, 10,1%). A alta prevalência de FeLV demonstrada neste estudo destaca a necessidade de estabelecer estratégias eficazes de controle e prevenção na região para reduzir os fatores de risco de transmissão. [resumo fornecido pelo autor]
Keywords: Vírus da leucemia felina; Retrovírus; Reação em cadeia de polimerase; Gatos - Infecções - Caxias do Sul (RS); Leukemia Virus, Feline; Retroviridae; Polymerase chain reaction; Cats - Infections - Caxias do Sul (Brazil)